ISOLASI DAN IDENTIFIKASI SENYAWA GOLONGAN FLAVONOID PADA DAUN NANGKA (Artocarpus heterophyllus Lmk) DAN AKTIVITAS ANTIBAKTERI TERHADAP BAKTERI Staphylococcus aureus - Darmawati, Anak Agung Sagung Krisna; Bawa, I Gusti Agung Gede; Suirta, I Wayan (Jurnal Kimia (Journal of Chemistry), 2015)
Isolation, identification and antibacterial activity of flavonoid compounds from jackfruit leaf (Artocarpus heterophyllus Lmk) extract have been done in this research. Extraction of 500 g dry powder of jackfruit leaf using maceration method produced 31.20 g concentrated brownish green ethanol extract. Partition of 30.00 g the ethanol extract gained three concentrated extracts in n -hexane (4.46 g), chloroform (0.84 g) and n -buthanol (6.65 g) fractions. The phytochemical test showed that n -buthanol extract contained flavonoid compound which was active as antibacterial agent with 15.75 mm inhibition capacity. Column chromatography analysis on n -buthanol extract with mobile phase n -hexana: ethyl acetate: n -butanol (8:2:1) gave 8 fractions (FA, FB, FC, FD, FE, FF, FG, FH).  Phytochemical testing showed that fraction FA and fraction FH belong to flavonoide compounds. Analysis of FA using UV-Visible gained 2 peaks at ? 323.40 nm (band I) and ? 285.60 nm (band II) which indicated the flavonoide groups of flavanone or dihydroflavonol. Analysis of FH using UV-Visible gained 2 peaks at ? 323.40 nm (band I) and ? 285.60 nm (band II) suggested the flavonoide groups of flavone or flavonol (3-OH substitution).` By using shiffting reagent the isolate FA was suggested to contain dihydroflavonol group and FH was suggested to contain flavone with hydroxyl groups at C-2’, C-4’.C-5’, C-6’, C-6, C-7, and C-8. Infrared analysis showed that the isolate had –OH, C=O, C-O, C=C aromatic, CH aromatic, and CH aliphatic groups. Antibacterial testing of flavonoid compounds of fraction A and fraction H on Staphylococcus aureus with a concentration of 10.000 ppm inhibited 10.50 mm for fraction A and 7.25 mm for fraction H.
Keywords: Dihidroflavonol, Flavone, Artocarpus heterophyllus Lmk., Antibacterial, Staphylococcus aureus